Penerapan Formulasi Pembuatan Pupuk Polychar Plus Granule Di Tefa Rintisan Rumah Organik - Sugiyarto Sugiyarto; Descha Giatri Cahyaningrum; Ni nengah Putri Adnyani; Ramadhan Taufika; Qanitah Qanitah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Fertilizer is a vital component in supporting agricultural productivity; however, low soil fertility and farmers’ dependence on synthetic chemical fertilizers have long-term negative impacts on soil health, the environment, and overall productivity. Therefore, an environmentally friendly and sustainable fertilizer innovation is required. Polychar Plus Granule fertilizer was developed as an alternative based on biochar enriched with macro- and micronutrients, and formulated in granule form for more practical application. Biochar functions as a soil conditioner that improves cation exchange capacity (CEC), maintains soil moisture, and supports the growth of beneficial soil microorganisms. The addition of organic materials and minerals (N, P, and K) enables this fertilizer to not only improve soil structure but also supply plants with balanced nutrition. This community service activity was carried out through training, demonstration of fertilizer formulation, and field mentoring at the partner farm Tefa Rintisan Rumah Organik. The main objectives were to: (a) enhance sustainable soil fertility, (b) reduce dependency on chemical fertilizers, (c) provide appropriate technology based on local resources (activated charcoal, organic waste, rice husk ash, etc.), and (d) increase production economically. The expected outputs include publication in an ISBN-proceeding at the National Seminar on Research and Community Service (NaCosVi) Politeknik Negeri Jember 2025, activity videos uploaded to the P3M Politeknik Negeri Jember YouTube channel, coverage in the Radar Jember online media, and an article published in an accredited community service journal. It is expected that Polychar Plus fertilizer technology can be independently adopted by farmers as an alternative solution to support sustainable agricultural systems.